Fetal MRI findings in a retrospective cohort of 26 cases of prenatally diagnosed CHARGE syndrome individuals. (3rd April 2019) - Millischer, Anne‐Elodie; Sonigo, Pascale; Attie, Tania; Spaggiari, Emmanuel; O'Gorman, Neil; Bessieres, Bettina; Kermorvant, Elsa; Boddaert, Nathalie; Salomon, Laurent‐Julien; Grevent, David
Abstract: "CHARGE syndrome" (CS) is a multifaceted syndrome associated with a poor prognosis. The prenatal diagnosis remains challenging especially as the fetal anomalies that may evoke suspicion of CS are not comprehensively described. Objective: This study aims to identify the anomalies in MRI with suspected CHARGE syndrome and to propose a possible standardization in the image‐based prenatal diagnosis of CS. Methods: This was a retrospective study of 26 fetuses who underwent MRI and had a confirmed diagnosis of CS, as proven by histopathological and/or neonatal examinations and/or the presence of the CHD7 gene mutation. Results: The three most frequent MRI anomalies confirmed at histopathological and/or neonatal examinations were arhinencephaly in 100% (26 of 26), dysplasia of the semicircular canals agenesis (SCA) in 100% (24 of 24), and posterior fossa anomalies in 100% (22 of 22). Our study also revealed short petrous bones with a particular triangular shape in 24 of 24 cases of SCA. Other relevant findings included external ear anomalies in 36% (9 of 25), cleft lip and palate (9 of 9), ventriculomegaly (VMG) (6 of 6), short corpus callosum (3 of 3), and ocular asymmetry in 36.6% (4 of 11). Conclusion: Our study emphasizes the interest of fetal MRI in the diagnosis of CS with an adapted knowledge of semiology. Abstract : What's already known about this topic? Fetal MRI has emerged as an extremely accurate imaging modality in fetal prenatal neurological diagnosis. As CHARGE syndrome is a rare but severe condition, its diagnosis remains challenging prenatally. What does this study add? Given of the difficulty of making this diagnosis prenatally and the importance of prenatal counselling especially in this setting, our findings demonstrate that targeted fetal MRI has a major role in providing an accurate diagnosis following ultrasound, even more so when a tailored MRI protocol is implemented